2007
DOI: 10.1523/jneurosci.4765-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Gene Expression Correlates of Social Behavior in Monkeys Experiencing Maternal Separation

Abstract: Children exposed to early parental loss from death or separation carry a greater risk for developing future psychiatric illnesses, such as major depression and anxiety. Monkeys experiencing maternal separation at 1 week of age show fewer social behaviors and an increase in self-comforting behaviors (e.g., thumb sucking) over development, whereas in contrast, monkeys experiencing maternal separation at 1 month of age show increased seeking of social comfort later in life. We sought to identify neural systems th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 54 publications
5
132
0
Order By: Relevance
“…Importantly, early-life FGF2 treatment also enhanced adult neurogenesis, which was accompanied by increased hippocampal expression of NTRK3 (55). Moreover, primate research has demonstrated that neurodevelopmentally relevant gene expression in the amygdala is altered by prolonged maternal separation (57). Taken together, these data are consistent with our demonstration that monkeys with lower levels of AT show greater Ce expression of NTRK3 and further motivate mechanistic research into the role for neurodevelopmentally important transcripts in the development of AT.…”
Section: Resultssupporting
confidence: 89%
“…Importantly, early-life FGF2 treatment also enhanced adult neurogenesis, which was accompanied by increased hippocampal expression of NTRK3 (55). Moreover, primate research has demonstrated that neurodevelopmentally relevant gene expression in the amygdala is altered by prolonged maternal separation (57). Taken together, these data are consistent with our demonstration that monkeys with lower levels of AT show greater Ce expression of NTRK3 and further motivate mechanistic research into the role for neurodevelopmentally important transcripts in the development of AT.…”
Section: Resultssupporting
confidence: 89%
“…In monkeys, infants deprived of their mothers exhibit a striking decrease in social interactions with others and an increase in self-comforting behaviors [1][2][3]. In adults, nonverbal "selfadaptors" are unintentional movements that involve self-touching behaviors such as stroking or rubbing one's own hand, and are associated with a lack of conscious awareness, occurring in response to situational anxiety and stress [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, poor caregiving in rodents results in acceleration of amygdala development (9,10), increases in corticotrophin-releasing hormone-containing neurons (11), and sensitization of the amygdala in adolescence (12). In addition, nonhuman primate studies show that maternal separation alters amygdala development, and that this effect is more devastating when maternal separation occurs earlier in life (13).…”
mentioning
confidence: 99%